RTs across Dual Stimuli, Gender, GPA and Trialt-ype - Hartanto Hartanto (Jurnal Psikologi, 2018)
This psychophysics experiment of the Eriksen Flanker Task experiment is built in four independent variables (stimuli, gender, GPA, and trial-type) with one dependent variable (RTs). CAF was also examined between stimuli arrow and letter. The data was analyzed using the four-way ANOVA. The result revealed that 1) Arrow stimuli needed few RTs than letter stimuli (F value = 17.964, and p-value = 2.34e-05). 2) In gender, there was a significantly different effect of RTs between female and male groups(F value = 91.203, p-value = 2e-16 (p < 0.001). 3) In trial-type, incongruent trial required more RTs than congruent trial (F value = 144.569, p-value = <2e-16 (p < 0.001). 4) Arrow stimuli was more accurate than letter with t-value = 6.4099, df = 2220.5, p-value = 1.773e-10. The result found the differences between the stimuli were caused by horizontal and vertical attention, so were in trial-type with parallel and focus phase. Across gender, the male group has proven to be faster in both stimuli than the female counterpart. This RTs pattern suggests that in conflict flanker task research, people tend to show the same architecture processing. Therefore the finding is quite universal in many research.